Indices for antioxidant enzymes activity and yield attributes of mash bean [Vigna mungo L. Hepper] genotypes under rhizospheric intensified lead (Pb) concentrations - Yasin, Ghulam; Fatima, Samreen; Saher, Amna; Nokhaiz, Gul; Khan, Aqsa (Journal of Pure and Applied Agriculture, 2023)
This study was designed to evaluate the toxicity extent of various Pb2+ concentrations with emphasis on genotypic variations. Four genotypes of mash bean i.e. Mash 80, Mash 88, Mash 97 and Mash ES-1 were grown in pots with four replicates. After twenty days of germination, various concentrations of lead (10, 20, 30, 40, 50 and 60 mg kg-1 ) were added in soil as Pb (NO3)2. Increasing amount of Pb2+ from 10 mg kg-1 showed a gradual significant reduction in legume setting, grain numbers and total yield. The lowest overall reduction was observed under imposition of 10 mg kg-1 as 3.719% in legume number, 3.153% in grain number and 6.823% in total yield. The maximum reduction in yield attributes was recorded at 60 mg kg-1 in legume number (73.761%), in grain number (71.179%) and in total yield (92.326%). Among the genotypes, Mash 88 was the most productive for various yield attributes, while Mash ES-1 was least productive. The activity of antioxidant enzymes showed a linear correlation with metal concentration. Ascorbate peroxidase (APOX) increase was 11.611% at 40 mg kg-1 , 32.81% at 50 mg kg-1 and 49.503% at 60 mg kg-1 . Superoxide dismutase (SOD) increase was 14.911% at 40 mg kg-1 , 31.939% at 50 mg kg-1 ) and 50.058% at 60 mg kg-1 . Catalase (CAT) increase was 7.092% at 30 mg kg-1 , 13.288% at 40 mg kg-1 , 18.239% at 50 mg kg-1 and 30.140% at 60 mg kg-1 . Superoxide dismutase and catalase activities were higher in genotypes Mash 88 as 7.451U mg/g and 34.544 U mg/g, respectively than that in other genotypes, while the least antioxidant activity was noted in Mash ES-1. These findings reflect the criteria for selection of the land regarding toxicity extent of Pb2+ to grow mash bean in future. © 2020 Department of Agricultural Sciences, AIOU